Design and Analysis of Propeller Blade for Aircrafts - Renjith Nimal, R.J. Golden; Venkatesan, A. (International Journal of Psychosocial Rehabilitation, 2019)
In order to conserve natural resources and economize energy, weight reduction has been the main focus of aerospace manufacturers in the present scenario. Weight reduction can be achieved primarily by the introduction of better material, design optimization and better manufacturing processes. The propeller blade is one of the potential items for weight reduction in aerospace as it accounts for 10% - 20% of the unspring weight. This achieves the aircraft with more fuel efficiency and improved riding qualities. The introduction of metal alloys was made it possible to reduce the weight of blade without any reduction on load carrying capacity and stiffness. Since, the composite has more elastic strain energy storage capacity and high strength to weight ratio as compared with those of aluminium, it can used as the blades for aerospace. Modelling and analysis of the composite blade will be done in this project.